Initial Treatment Response in Ocular Myasthenia Gravis: A Comparison Between Low and Moderate Doses of Prednisolone - Threetong T (Dove Medical Press, 2020)
Thanatporn Threetong,1,2 Anuchit Poonyathalang,1 Pisit Preechawat,1 Panitha Jindahra,3 Tanyatuth Padungkiatsagul,1 Kavin Vanikieti1 1Department of Ophthalmology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Department of Ophthalmology, Faculty of Medicine, Burapha University, Chonburi, Thailand; 3Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Tanyatuth PadungkiatsagulDepartment of Ophthalmology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Bangkok 10400, ThailandTel +662 201 1526Fax +662 201 2729Email blu_c16@hotmail.comPurpose: To evaluate the initial treatment response to low doses of prednisolone, compared with moderate doses, in ocular myasthenia gravis (OMG).Patients and Methods: A retrospective chart review of patients with adult-onset (age ≥ 15 years old) OMG, who were treated with prednisolone, was conducted. Subjects were divided into two groups according to their prednisolone dosing regimen. The low-dose group was defined as those with an average 12-week cumulative dose of prednisolone < 0.435 mg/kg/day and the moderate-dose group averaged 0.435– 1.000 mg/kg/day. The primary outcome of interest was the comparison of clinical response to prednisolone at 12 weeks between the low-dose and moderate-dose groups. The secondary outcome was the difference in adverse events between treatment groups.Results: Of 34 subjects, 16 subjects (47.1%) were male. The mean age at onset was 44.0± 18.1 years. The most common presenting ocular feature was ptosis with ophthalmoplegia (22 subjects, 64.7%), followed by isolated ptosis (nine subjects, 26.5%) and isolated ophthalmoplegia (three subjects, 8.8%). Half of the subjects were treated with low-dose prednisolone and the other half were treated with moderate-dose prednisolone. There were no substantial differences in baseline characteristics between treatment groups. After 12 weeks of treatment, nine of 17 subjects (52.9%) and 13 of 17 subjects (76.5%) in the low- and moderate-dose groups, respectively, were regarded as responsive to the prednisolone treatment (P=0.28). Adverse events were exclusively observed in the moderate-dose group.Conclusion: Treatment of OMG with an average 12-week cumulative dose of prednisolone < 0.435 mg/kg/day (low dose) shows a comparable responsive outcome to 0.435– 1.000 mg/kg/day of prednisolone (moderate dose). Treating OMG with low-dose prednisolone can minimize prednisolone-related adverse events. However, a prospective randomized controlled trial with a larger study population is warranted in order to gain more insight into the proper dosage of prednisolone for OMG.Keywords: ocular myasthenia gravis, low dose, moderate dose, prednisolone, treatment outcome